OVERVIEW OF ADDED VALUE-ADDED TAXES IN CONNECTION WITH COVID-19 VIRUS PLAGUE: VAT FACILITIES OR TAX INCENTIVES? - Andri Marfiana (Jurnal Manajemen STIE Muhammadiyah Palopo, 2020)
AbstrakPenelitian ini bertujuan untuk menjelaskan bagaimana berlakuya PMK-28/PMK.03/2020, berkaitan dengan PPN DTP sebagai fasilitas atau insentif PPN. Terjadi kerancuan pemahaman antara fasilitas PPN berdasarkan UU PPN dengan insentif PPN DTP. Walaupun demikian, peneliti mencoba menjelaskan alasan Pemerintah memberikan insentif PPN. Penelitian ini menggunakan pendektan metode pengumpulan data studi literatur. Untuk metode analisis yang digunakan yaitu dengan pendekatan deskriptif kualitatif. Hasil penelitian menunjukan bahwa penerapan PMK-28/PMK.03/2020 didasari oleh inisiatif cepat Pemerintah dalam menanggulangi wabah Covid-19. Penelitian menunjukan bahwa insentif PPN DTP, tidak termasuk dalam fasilitas yang diatur oleh UU PPN. Akan tetapi, pemberian insentif ini berusaha tidak melanggar aturan yang diatur oleh UU PPN. Hal ini dapat terlihat mekanisme PK-PM tetap berjalan, walaupun atas beban PK ditanggung oleh Pemerintah. Dalam penelitian ini, dapat dismpulkan bahwa penerapan PMK-28/PMK.03/2020 adalah pemberian insentif pajak dan bukan fasilitas PPN sebagaimana ditur dalam UU PPN.Kata Kunci: Covid-19, Korona 2020, PMK-28 2020, Tax Incentive, Tax.AbstractThis study aimed to explain how the PMK-28 / PMK.03 / 2020 applies, relating to the PPN DTP as a VAT facility or incentive. There is a confusion between the understanding of VAT facilities based on the VAT Act and the PPN DTP incentives. Nevertheless, the researchers tried to explain the government's reasons for providing VAT incentives. This research using a literature study data collection method. The analytical method used is a qualitative descriptive approach. The results showed that the application of PMK-28 / PMK.03 / 2020 was based on the government's rapid initiative in tackling the Covid-19 outbreak. Research indicates that PPN DTP incentives are not included in the facilities regulated by the VAT Law. However, the granting of this incentive tries not to violate the rules governed by the VAT Law. It can be seen by the mechanism of PK-PM still running, even though the government bears the burden of PK. In this study, it can be concluded that the application of PMK-28 / PMK.03 / 2020 is the provision of tax incentives and not VAT facilities, as stipulated in the VAT Law.Keywords: Covid-19, Corona 2020, PMK-28 2020, Tax Incentive, Tax.